Kehidupan Masyarakat Modern: Sorotan Alkitab terhadap Peradaban Masyarakat di Era Modern - Novianti, Nunuk (Jurnal Arrabona, 2025)
Modernization that offers convenience and efficiency often causes individuals, especially Christians, to experience difficulties in maintaining a connection with the spiritual values contained in the Bible. The novelty of this study lies in the systematic attempt to explore how the Bible can serve as a moral and spiritual guide in facing the challenges of modernity. The main objective of this study is to explore and analyze the role of the Bible and provide practical recommendations for Christians to apply the values of the Bible in their daily lives and foster deeper spiritual engagement. The research method used in this study is descriptive qualitative, which aims to gain an in-depth understanding of the phenomenon of Bible reading practices and spiritual engagement among adult Christians. Data was collected through analyzing various sources available on the internet, including social media such as Instagram and comments on live streaming videos on YouTube. The results show that the Bible can be a source of inspiration and life guidance for Christians in facing modernization. The Bible provides values and teachings that are relevant in facing the challenges of modernization. The results also show that Christians can use the Bible as a life guide in facing modernization by: reading and meditating on the Bible regularly, using the Bible as a source of inspiration in facing challenges, making decisions based on the teachings of the Bible.